2020
DOI: 10.3390/mi11040346
|View full text |Cite
|
Sign up to set email alerts
|

Self-Aligned Hierarchical ZnO Nanorod/NiO Nanosheet Arrays for High Photon Extraction Efficiency of GaN-Based Photonic Emitter

Abstract: Advancements in nanotechnology have facilitated the increased use of ZnO nanostructures. In particular, hierarchical and core–shell nanostructures, providing a graded refractive index change, have recently been applied to enhance the photon extraction efficiency of photonic emitters. In this study, we demonstrate self-aligned hierarchical ZnO nanorod (ZNR)/NiO nanosheet arrays on a conventional photonic emitter (C-emitter) with a wavelength of 430 nm. These hierarchical nanostructures were synthesized through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
(37 reference statements)
0
3
0
Order By: Relevance
“…This is due to their outstanding properties, such as high efficiency and high stability. 1–3 Among various applications, the display is one of the industries in high demand for III-nitride PEs. The first use of III-nitride PEs as a display light source was in backlight units (BLUs) of the liquid crystal display (LCD) panel.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to their outstanding properties, such as high efficiency and high stability. 1–3 Among various applications, the display is one of the industries in high demand for III-nitride PEs. The first use of III-nitride PEs as a display light source was in backlight units (BLUs) of the liquid crystal display (LCD) panel.…”
Section: Introductionmentioning
confidence: 99%
“…Nine of the papers, [ 4 , 5 , 6 , 7 , 8 , 9 , 10 , 11 , 12 ], explore various designs of wide bandgap high power devices. The remaining papers cover various applications based on wide bandgaps, such as ZnO Nanorods for High Photon Extraction Efficiency of GaN-Based Photonic Emitter [ 13 ], InGaZnO Thin-Film Transistors [ 14 ], Wide Band Gap WO 3 Thin Film [ 15 ], Silver Nanorings [ 16 , 17 ] and InGaN Laser Diode [ 18 , 19 , 20 ].…”
mentioning
confidence: 99%
“…Besides, Lee et al [ 13 ] demonstrated self-aligned hierarchical ZnO nanorod nanosheet arrays on a conventional photonic emitter with a wavelength of 430 nm with an improved optical output power. Zhang et al [ 14 ] improved the electrical performance and bias-stress stability of amorphous InGaZnO thin-film transistors using buried-channel devices with multiple-stacked channel layers.…”
mentioning
confidence: 99%